The sanctuary - Engberg, Katrine, 1975- (Scout Press, 2023)
While staying in Bornholm for the winter, Jeppe Kørner is drawn into a sinister mystery rooted in the past when an investigation into a severed corpse in Copenhagen leads Anette Werner to this seemingly peaceful refuge, and together they must unravel the island's secrets to stop a brutal killer.